An application of land suitability evaluation for FTDP: a fuzzy MCDM approach. (4th January 2010) - Chaddad, Ibrahim; Feng, Chen Bao; AL-Husni, Majdi; Zhen, Ren Jin
The main objective of this paper is to carry out Multi-Criteria Decision Making (MCDM) to arrive at the best alternative by accounting for uncertainties and spatial variability in the various elements. The present paper focuses on addressing uncertainty in the process of land suitability evaluation for horticultural projects area (mountains area in Syria). In this context, both fuzzy AHP and TOPSIS methods are applicable in determining agricultural land-use priorities and can be used in the planning process. Setting priorities or ranking agricultural land use (by area) is a complex task in the frame of sustainable development. All the methodologies are implemented to analyse the suitability of the horticultural crop in different areas in Syria.